Narrow windrow burning canola (Brassica napus L.) residue for Sclerotinia sclerotiorum (Lib.) de Bary sclerotia destruction - Brooks, K.; Bennett, Sarita; Hodgson, L.; Ashworth, Michael (John Wiley & Sons Ltd., 2018)
© 2018 Society of Chemical Industry BACKGROUND: Since the introduction of herbicide-tolerant varieties of canola (Brassica napus L.) in 1993, global plantings have increased resulting in an increased incidence of Sclerotinia sclerotiorum (Lib.) de Bary infections. Developments in narrow windrow burning techniques to destroy the seed of multiple herbicide-resistant weeds provide an opportunity to also intercept and heat-treat the S. sclerotiorum inoculum source, termed sclerotia, before it re-enters the soil to infect susceptible crop species in successive years. RESULTS: Preliminary kiln studies determined that a temperature of 264 °C for 10 s was needed to destroy S. sclerotiorum sclerotia viability (LT99) of sclerotia < 3 mm in diameter, whereas temperatures of 353 and 362 °C for the same duration were required to kill sclerotia (LT99) of 3–4 and > 4 mm in diameter respectively. In the field, temperatures > 500 °C were maintained in the centre of burning narrow windrows of canola residue for > 450 s and 300 °C was maintained consistently at either edge of the windrows for the same duration. The temperatures achieved when burning canola narrow windrows were sufficient to kill all sclerotia concentrated into the narrow windrow. CONCLUSION: As a technique, narrow windrow burning of canola residue provides the temperature and temperature durations required to kill S. sclerotiorum sclerotia, thus providing a non-fungicidal control option as part of a wider integrated disease management approach. © 2018 Society of Chemical Industry.